2005
DOI: 10.1021/tx050126f
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis of Murine Pulmonary Tissue Following Carbonyl Chloride Inhalation

Abstract: Carbonyl chloride (phosgene) is a toxic industrial compound widely used in industry for the production of synthetic products, such as polyfoam rubber, plastics, and dyes. Exposure to phosgene results in a latent (1−24 h), potentially life-threatening pulmonary edema and irreversible acute lung injury. A genomic approach was utilized to investigate the molecular mechanism of phosgene-induced lung injury. CD-1 male mice were exposed whole body to either air or a concentration × time amount of 32 mg/m3 (8 ppm) ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 18 publications
(33 reference statements)
9
62
0
Order By: Relevance
“…Indeed, recent reports from our lab [19,20] and from others [21][22][23] have shown that Ch25h is up-regulated rapidly and significantly in the lungs of mice in response to a pathogen or to a nonpathogen challenge. Although it is clear that Ch25h expression is induced under a variety of conditions, the cellular sources and molecular mechanisms that control this expression are yet to be defined.…”
Section: Introductionmentioning
confidence: 89%
“…Indeed, recent reports from our lab [19,20] and from others [21][22][23] have shown that Ch25h is up-regulated rapidly and significantly in the lungs of mice in response to a pathogen or to a nonpathogen challenge. Although it is clear that Ch25h expression is induced under a variety of conditions, the cellular sources and molecular mechanisms that control this expression are yet to be defined.…”
Section: Introductionmentioning
confidence: 89%
“…Analysis of variance (ANOVA) P values were calculated by using Partek Genomics Suite software (St. Louis, MO). A mixed model two-way ANOVA (13) was used to compare miRNA expression profiles preexposure vs. postexposure by using subject identification as a random effect, similar to microarray analyses performed in previous investigations (32,39). To control the rate of false positives, q-values were calculated as the minimum "false positive discovery rate" that can occur when identifying significant hypotheses (41).…”
Section: Methodsmentioning
confidence: 99%
“…-, Data from 10-min exposures were excluded in the concentration-time-response analysis used in the "toxic load model." synthesis of glutathione and redox regulation, arachidonic acid metabolism, the release of proinflammatory cytokines, and cytoskeletal effects (F-actin organization) Franch & Hatch, 1986;Currie et al, 1985Currie et al, , 1987aCurrie et al, , 1987bGhio et al, 2005;Sciuto et al, 2002;Sciuto et al, 2003aSciuto et al, , 2003bSciuto et al, , 2003cSciuto et al, 2005;Duniho et al, 2002;Deshpande et al, 1996;Madden et al, 1991;Werrlein et al, 1994). Phosgeneinduced apoptotic changes in pneumocytes and inflammatory cells were described (Li et al, 2006).…”
Section: Inhalation Toxicity Of Phosgene In Experimental Modelsmentioning
confidence: 99%